Agonistic and potentiating effects of perfluoroalkyl substances (PFAS) on the Atlantic cod (Gadus morhua) peroxisome proliferator-activated receptors (Ppars). (May 2022) - Søderstrøm, Sofie; Lille-Langøy, Roger; Yadetie, Fekadu; Rauch, Mateusz; Milinski, Ana; Dejaegere, Annick; Stote, Roland H.; Goksøyr, Anders; Karlsen, Odd André
Graphical abstract: Abstract: Toxicity mediated by per- and polyfluoroalkyl substances (PFAS), and especially perfluoroalkyl acids (PFAAs), has been linked to activation of peroxisome proliferator-activated receptors (Ppar) in many vertebrates. Here, we present the primary structures, phylogeny, and tissue-specific distributions of the Atlantic cod ( Gadus morhua ) gmPpara1, gmPpara2, gmPparb, and gmPparg, and demonstrate that the carboxylic acids PFHxA, PFOA, PFNA, as well as the sulfonic acid PFHxS, activate gmPpara1 in vitro, which was also supported by in silico analyses. Intriguingly, a binary mixture of PFOA and the non-activating PFOS produced a higher activation of gmPpara1 compared to PFOA alone, suggesting that PFOS has a potentiating effect on receptor activation. Supporting the experimental data, docking and molecular dynamics simulations of single and double-ligand complexes led to the identification of a putative allosteric binding site, which upon binding of PFOS stabilizes an active conformation of gmPpara1. Notably, binary exposures of gmPpara1, gmPpara2, and gmPparb to model-agonists and PFAAs produced similar potentiating effects. This study provides novel mechanistic insights into how PFAAs may modulate the Ppar signaling pathway by either binding the canonical ligand-binding pocket or by interacting with an allosteric binding site. Thus, individual PFAAs, or mixtures, could potentially modulate the Ppar-signaling pathway in Atlantic cod by interfering with at least one gmPpar subtype.